EFFECTS OF PROPAGATING SUBMERGED OBJECTS ON DIFFUSIVE STAIRCASES - Davis, James E. (Monterey, CA; Naval Postgraduate School, 2018)
Reissued 3/14/2019 with corrections to the abstract. With the Arctic ice pack melting, and the realization of vast economic opportunity becoming apparent, the U.S. Navy may deploy warships in the Arctic Ocean to protect American national interests. Before entering a new area of operations, a thorough study of the environment should take place in order to maintain a competitive advantage over potential adversaries. A feature of the Arctic Ocean that merits advance study is thermohaline staircases, which have been identified as one of the key processes affecting the diapycnal heat transport in the high-latitude oceans and, ultimately, the melting of the sea-ice. Thermohaline staircases are commonly occurring in the main halocline of the Arctic Ocean. This study uses numerical simulations to model an object travelling through diffusive staircases to understand the resilience of staircases, their ability to maintain the vertical heat transport, and the ability to detect the persistent hydrodynamic signatures of propagating submersibles. The results show that hydrodynamic signatures of a submerged object travelling through a staircase can be detected long after its passage. The time it takes for the thermohaline staircase to reform depends critically on both characteristics of the submersible and the environmental parameters. Approved for public release; distribution is unlimited. Lieutenant, United States Navy http://archive.org/details/effectsofpropaga1094559647